The Development of Novel Model Systems and Imaging Techniques to Advance the Understanding of Calcific Aortic Valve Disease - Baugh, Lauren. (2018)
Abstract: As a leading cause of cardiovascular morbidity and mortality, calcific aortic valve disease (CAVD) is responsible for significant health and cost burden around the world. While valve replacement surgery can improve quality of life and increase life expectancy, it is not without risks and costs. However, this is currently the only method available to treat CAVD since a lack of understanding surrounding the disease mechanisms has hindered the development of pharmaceutical interventions. In order to improve our understanding of valve stenosis and calcification, in the hopes of expanding the range of treatment methods for CAVD, we study several aspects of the disease and have developed an imaging method that non-destructively captures mineralization in tissues and in vitro culture. Stenosis and calcification of valve tissue is accompanied by significant changes to the extracellular matrix (ECM) structure and composition. To discern how these variations in ECM could affect valve interstitial cells (VICs) - the most abundant cell type in valve tissue - we developed both in vitro and in vivo model systems. A 2D, polyacrylamide (PAAM) gel-based cell culture platform showed that hyaluronic acid (HA), an ECM protein found in large abundance in the aortic valve, increased VIC mineralization, but that effect could be mitigated through siRNA knockdown of the HA binding protein CD44. We also developed a Tie2-cre mediated conditional knockout (cKO) of the retinoblastoma protein (pRb) in a mouse model which, compared to control mice, showed increased aortic valve stenosis with age. Significant alterations to the valve leaflet ECM organization and protein composition (as measured by proteomics analysis) were also seen in cKO pRb mice leading to the conclusion that this mouse model may be a useful system for studying CAVD. To further visualize changes to aortic valve tissue, we also developed a novel imaging technique that used endogenous two-photon excited fluorescence signal from calcific nodules to measure mineralization content. We termed this the mineralization associated fluorescence (MAF). MAF as a quantitative measure of calcification was confirmed using human and mouse valve tissue, rat bone, and the 2D PAAM gel in vitro model system. Interestingly, time lapse imaging of our in vitro cell culture platform allowed us to measure calcific nodule growth in real time. During the course of the experiment, we noted varying rates of development and growth rates of mineralization which further emphasizes the variability that can occur during valve calcification. Lastly, to further the understanding of the effect ECM proteins can have on valve mineralization, we created a methacrylated hyaluronic acid (MeHA)-based 3D model. To investigate cell response, we can incorporate ECM proteins, identified through the transcriptomic approach of RNA sequencing, into the MeHA gels. Utilizing VICs, we can evaluate the effect of MeHA gel composition on mineralization over time. Using the non-destructive imaging approach that we developed, as well as other nonlinear microscopy techniques, we can track calcification and cell response. Overall, the research described in this thesis highlights the importance of taking a multipronged approach to further the understanding of CAVD with the goal of developing more effective treatment methods.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Lauren Black.; Committee: Elena Aikawa, Irene Georgakoudi, Philip Hinds, and Gordon Huggins.; Keyword: Biomedical engineering.